2006
DOI: 10.1200/jco.2005.05.2530
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response in Radiotherapy for Localized Prostate Cancer: Results of the Dutch Multicenter Randomized Phase III Trial Comparing 68 Gy of Radiotherapy With 78 Gy

Abstract: This multicenter randomized trial shows a significantly improved FFF in prostate cancer patients treated with a higher dose of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
440
5
28

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(487 citation statements)
references
References 35 publications
14
440
5
28
Order By: Relevance
“…The additional strengths of the present study include higher radiation doses and longer follow-up. Dose-escalated RT has been shown to improve FFBF through better local control (20)(21)(22). This benefit with higher doses might allow differences in local control related to secondary factors, such as the NTDR, to be more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The additional strengths of the present study include higher radiation doses and longer follow-up. Dose-escalated RT has been shown to improve FFBF through better local control (20)(21)(22). This benefit with higher doses might allow differences in local control related to secondary factors, such as the NTDR, to be more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…There are now three published PSA-era Phase III prostate cancer radiation dose escalation series (8,28,29). All have shown an improvement in freedom from biochemical failure with higher radiation doses.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple randomized clinical trials have demonstrated a dose escalation benefit for prostate radiotherapy (1)(2)(3)(4)(5). Recent data suggests both inter-and intra-fraction prostate motion is not negligible (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%